A new, simple, highly scalable, and efficient protocol for genomic DNA extraction from diverse plant taxa. (7th April 2021) - Mavrodiev, Evgeny V.; Dervinis, Christopher; Whitten, William Mark; Gitzendanner, Matthew A.; Kirst, Matias; Kim, Sangtae; Kinser, Taliesin J.; Soltis, Pamela S.; Soltis, Douglas E.
Abstract : Premise: Commonly used molecular techniques such as next‐generation sequencing require reliable methods to extract DNA quickly and efficiently. Secondary compounds within plant tissues make this requirement all the more challenging, often forcing researchers to test different extraction methods tailored to their particular species of interest in order to obtain large amounts of high‐quality genomic DNA. The opportunities provided by high‐throughput, next‐generation sequencing only exacerbate these problems, especially when trying to extract DNA from multiple species at the same time. Several methods have attempted to resolve the challenges of obtaining suitable DNA from plants; however, a rapid, high‐yield, high‐quality, and highly scalable DNA extraction method is still needed. Methods and Results: We present a rapid DNA extraction protocol that utilizes a buffer with relatively large amounts of cetyltrimethylammonium bromide (CTAB) and sodium chloride, combined with a silica maxi‐column cleanup of the extracted DNA. The new method is easy to implement using standard equipment and inexpensive reagents. The entire procedure (from grinding to the final elution) can be completed in less than two hours for a single sample and can be easily scaled to meet desired research goals. It works on diverse green plants with highly varied secondary chemistries (e.g., ferns, gymnosperms, and phylogenetically divergent angiosperms). Conclusions: Application of the protocol to various plant species yielded DNA of high quality in less than two hours and can be adjusted to extract DNA at large (maxi‐preps) or small (96‐well minipreps) scales. We anticipate that our method will be of wide utility for rapidly isolating large quantities of quality genomic DNA from diverse plant species and will have broad applications in phylogenetic studies utilizing PCR and short‐read DNA sequencing.